Histological chorioamnionitis is predicted by early infant C‐reactive protein in preterm infants and correlates with neonatal outcomes. (28th September 2019) - Ryan, Emer; Eves, Doireann; Menon, Poornima Jayadev; Alnafisee, Sarah; Mooney, Eoghan E.; Downey, Paul; Culliton, Marie; Murphy, John F. A.; Vavasseur, Claudine; Molloy, Eleanor J.
Abstract: Aim: Histological chorioamnionitis (HCA) is associated with preterm birth and adverse neonatal outcomes. We evaluated the rise in C‐reactive protein (CRP) in preterm infants as a predictor of HCA severity and outcomes. Methods: Consecutive preterm infants, born January 2009 to January 2014 in the National Maternity Hospital, Dublin, under 32 weeks' gestation or <1.5 kg birthweight, were included. Histological chorioamnionitis was staged as maternal inflammatory response, foetal inflammatory response and non‐HCA. Results: Preterm infants (n = 518) were included with a mean gestational age 28.5 ± 2.8 weeks, birthweight 1.1 ± 0.3 kg, and 53.5% were male. Histological chorioamnionitis was found in 25.4%. Histological chorioamnionitis was present in 93.7% when CRP > 5 mg/L, 65.2% when CRP 1‐5 mg/L and in 19.4% when CRP < 1 mg/L. When both the immature to total neutrophil (IT) ratio was >0.2 and the CRP > 1 mg/L the positive predictive value and negative predictive value for HCA were 92.5% and 84.9%, respectively. Histological chorioamnionitis was associated with more resuscitation and respiratory distress syndrome (both P < .001). A CRP > 10 mg/L was associated with a foetal inflammatory response and increased early‐onset sepsis. Conclusion: Higher early CRP was a surrogate predictor of HCA and correlated with the severity of HCA. Higher CRP and HCA were associated with adverse early outcomes.